Current understanding of hypothalamic amenorrhoea. (July 2020) - Roberts, Rachel E.; Farahani, Linda; Webber, Lisa; Jayasena, Channa
Hypothalamic amenorrhoea (HA) accounts for approximately 30% of cases of secondary amenorrhoea in women of reproductive age. It is caused by deficient secretion of hypothalamic gonadotrophin-releasing hormone, which in turn leads to failure of pituitary gonadotrophin and gonadal steroid release. Functional HA (FHA) is defined as HA occurring in the absence of a structural lesion and is predominantly caused by significant weight loss, intense exercise or stress. Treatment of FHA is crucial in avoiding the long-term health consequences on fertility and bone health, in addition to reducing psychological morbidity. This article summarises our understanding of the mechanisms underlying FHA, the evidence base for its clinical management and emerging therapies.